2005
DOI: 10.3928/0098-9134-20051001-07
|View full text |Cite
|
Sign up to set email alerts
|

Wearing and Using Personal Emergency

Abstract: Frail older adults living alone are at risk for falling and not being found. A personal emergency response system (PERS) is a technological adjunct to home care for such individuals, but little is known of their experiences with the PERS. The experiences of seven frail women (ages 83 to 96) who lived alone were studied using a descriptive phenomenological method. The key phenomenon was temporizing about the PERS button, and the two component phenomena were deciding when to wear it and deciding whether to use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 21 publications
1
60
0
Order By: Relevance
“…The most common existing PERS, the push-button pendant, is not always satisfactory because during a loss of consciousness or a faint the pendant might not be activated [10]. Moreover, some elderly people do not activate their PERS, even when they have the ability to do so [11].…”
Section: Introductionmentioning
confidence: 99%
“…The most common existing PERS, the push-button pendant, is not always satisfactory because during a loss of consciousness or a faint the pendant might not be activated [10]. Moreover, some elderly people do not activate their PERS, even when they have the ability to do so [11].…”
Section: Introductionmentioning
confidence: 99%
“…These clinical alarm systems provide a way for individuals who fall to contact an emergency center by pressing a button. 16 While appropriate in many situations, the PERS system is rendered useless in the event that the person is unconscious or unable to reach the button. Even when the system is available, a recent cohort study found that around 80% of older adults wearing a PERS did not use their alarm system to call for help after experiencing a fall.…”
Section: Introductionmentioning
confidence: 99%
“…To address fall risk, the Personal Emergency Response System (PERS) [23,24] represents a commercial solution. These clinical alarm systems enable elderly people who fall to contact an emergency center by pressing a button.…”
Section: Ambient Assistive Technology For Indoor Fall Riskmentioning
confidence: 99%